Effect of Nb and Fe on damage evolution in a Zr-alloy during proton and neutron irradiation. (15th February 2019) - Francis, E.; Babu, R. Prasath; Harte, A.; Martin, T.L.; Frankel, P.; Jädernäs, D.; Romero, J.; Hallstadius, L.; Bagot, P.A.J.; Moody, M.P.; Preuss, M.
Abstract: Detailed analysis was carried out on proton and a neutron irradiated Nb-containing Zr-alloy to study the evolution of dislocation loop size and densities as well as the formation and evolution of irradiation-induced precipitation/clustering. The results obtained here have been contrasted against previously published work on a Nb-free Zr-alloy [1, 2] to investigate the mechanistic reason for the improved resistance to irradiation-induced growth of Nb-containing Zr alloys. The combined use of bright field scanning transmission electron microscopy, ultra-high-resolution energy dispersive spectroscopy and atom probe tomography analysis provides evidence of evenly distributed radiation-induced Nb clusters that have formed during the early stage of proton irradiation and Fe-rich nano-rods near Fe-containing second phase particles. The former seems to have a profound effect on loop and subsequent loop formation, keeping loop size small but number density high while loops seem to initially form at similar dose levels compared to a Nb-free alloy but loop line density does not increase during further irradiation. It is hypothesized that the formation of the Nb nano-precipitates/clusters significantly hinders mobility and growth of loops, resulting in a small size, high number density and limited ability of loops to arrange along basal traces compared to Nb-free Zr-alloys. It is suggested that it is the limited loop arrangement that slows down loop formation and the root cause for the high resistance of Nb-containing Zr-alloys to irradiation-induced growth. Graphical abstract: Image 1